A comparative study between the effects of adding dolomite as additive against thermal treatment on solidification of municipal solid waste bottom ash concrete / Mohd Syazwan Mohd Ghazali - Mohd Ghazali, Mohd Syazwan (2010)
Incineration bottom ash (lBA) may pollute soil, surface water or underground water if it contains toxic substances such as heavy metals. If this pollution is not appropriately managed, it can cause serious health risks and problem to the surrounding environment. In this study, incineration bottom ash from municipal solid waste (MSW) was used as a substitute to sand to form concrete-like material in a process known as solidification. Two methods of solidification were tested and examined. Four different composition of ash: sand ratio were used, i.e, (30:70), (50:0), (70:30) and (100:0). The solidification processes were evaluated by carrying out compressive strength and leaching tests . Results show that; of four different concrete produce, the (30:70) concrete was found to be best in term of strength and produced a lighter density material compare to normal concrete . Of the two solidification processes; thermally treatment performed better than addition dolomite as additive.